2020
DOI: 10.1039/d0ra04786d
|View full text |Cite
|
Sign up to set email alerts
|

Fully inkjet-printed multilayered graphene-based flexible electrodes for repeatable electrochemical response

Abstract: A fully inkjet printed and flexible multilayer graphene based three electrode device showed electrochemical reversibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 104 publications
1
24
1
Order By: Relevance
“…The achieved value of ρ is about 1.1 times higher than the resistivity of bulk platinum 1.06·10 −7 Ω∙m. In comparison with other studies [ 73 , 74 , 75 , 76 ], the developed platinum nano-ink shows lower values of resistivity after thermal sintering, see Table 3 .…”
Section: Resultscontrasting
confidence: 49%
See 1 more Smart Citation
“…The achieved value of ρ is about 1.1 times higher than the resistivity of bulk platinum 1.06·10 −7 Ω∙m. In comparison with other studies [ 73 , 74 , 75 , 76 ], the developed platinum nano-ink shows lower values of resistivity after thermal sintering, see Table 3 .…”
Section: Resultscontrasting
confidence: 49%
“…Indeed, the inset to Figure 11 shows that the Pt lines sintered at 750–900 °C have a high degree of sintering and low residual porosity. Additionally, it can be seen from comparative Table 3 that the developed nano-ink has a high concentration of particles (25 wt.%) in comparison with other studies [ 73 , 74 , 75 , 76 ], see Table 3 . The use of concentrated nano-ink is an additional advantage since it allows reducing the time for printing lines with a given resistance.…”
Section: Resultsmentioning
confidence: 70%
“…In the future, graphene would, thus, inevitably be the "magic lamp" of nanotechnology with utmost promise. [96] Copyright 2020, The Royal Society of Chemistry and Owner Societies 2020. (B) Fabrication of rGOFF@PANI conjugate non-woven fabric electrode, Reproduced with permission, [99] Copyright 2020, Elsevier Ltd.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators reported a wide pH range of stability, making it a superior IJP wearable sensor. [96] Laser-induced graphene (LIG), a three-dimensional, porous material, was constructed using direct laser writing, an ambient atmosphere, single step, graphene patterning, and preparation technique, reported by Ye et al. [97] The CO 2 laser was irradiated at the surface of the polyimide (PI) substrate, leading to a localized increase in the temperature (> 2500°C).…”
Section: Graphene-based Flexible Electronicsmentioning
confidence: 99%
See 1 more Smart Citation